Assessing Emotional Intelligence, Workplace Stress, and Health Outcomes in Clinical Postgraduate Trainees: A Study in Lahore’s Tertiary Care Hospitals - Syed Ahmed Mahmud, Fatima Aslam Shaikh, Sadia Chaudhary, Ahmed Foad Saeed, Aysha Foad Saeed, Qurrat Ul Ain Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Emotional intelligence (EI) plays a vital role in influencing general health (GHQ) and workplace stress across various professions, especially in healthcare. Clinical postgraduate trainees often experience high stress due to patient demands, emotional strain, and poor working conditions. Research suggests that individuals with higher EI manage stress better and enjoy improved health outcomes. Objectives: This study aimed to assess the relationship between EI, workplace stress, and general health status among clinical postgraduate trainees in Lahore’s tertiary care hospitals. It also evaluated gender and age differences and compared outcomes between high- and low-EI groups. Methods: A correlational, cross-sectional study was conducted at the University of Health Sciences, Lahore, from May to December 2015. A total of 241 FCPS trainees from various tertiary hospitals were included. Data were collected using validated questionnaires measuring EI, workplace stress, and GHQ. Results: Mean age was 28.86±2.57 years; 51.5% were male. EI was negatively correlated with stress but showed no correlation with GHQ or age. GHQ positively correlated with age. No significant gender differences were found in EI, stress, or GHQ. Conclusion: EI is inversely associated with workplace stress among clinical postgraduate trainees, regardless of age, gender, or general health, suggesting EI may buffer stress in demanding medical environments. Keywords: Emotional Intelligence, Stress, General Health, Postgraduate trainees, General health quality (GHQ).